UPAYA PENGENDALIAN STRES KERJA DALAM PENINGKATAN KINERJA JAKSA DI KEJAKSAAN NEGERI KLATEN (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
The research objectives are: (1) To determine the performance of the prosecutor at the Klaten District Attorney; and (2) To find out efforts to control work stress in improving the performance of the prosecutor at the Klaten District Attorney. Data collection techniques using observation, interviews and documentation. Interviews were conducted with 17 functional prosecutors serving in the Klaten District Attorney Office. Data analysis used descriptive qualitative analysis. The results showed: (1) The performance of the Public Prosecutor at the Klaten District Attorney in general was adequate, both from the aspect of the prosecutor work target and the aspect of work behavior. Based on the aspect of the prosecutor work target, it is known that the Prosecutor Office at the Klaten District Attorney has shown a fairly good quantity of work, namely the completion of the target agenda of cases that must be resolved, which on average reaches 2 -3 cases. The quality of their work is also maintained by taking into account the factors of suitability, neatness and completeness in accordance with existing SOPs and regulations. Based on the aspect of work behavior, it is known that the Prosecutor Office at the Klaten District Attorney has worked with the orientation of providing excellent service to the community and is able to cooperate with colleagues, superiors, work units and other agencies. They also maintain integrity, work with discipline and are able to cooperate with colleagues, superiors, other work units and other agencies. (2) Efforts to control work stress in improving the performance of prosecutors at the Klaten District Attorney are by applying stress management which includes individual handling strategies, organizational handling strategies and social support strategies.
Keywords: Work Stress Control; Performance